2011
DOI: 10.1108/13639511111106632
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making styles, stress and gender among investigators

Abstract: Purpose -The purpose of this study is to analyze the relationship between police investigators' decision-making styles, degree of judgmental self-doubt and work conditions, on the one hand, and their wellbeing, stress, burnout tendency and sleep quality, on the other. Design/methodology/approach -The study concerns investigative police officers (n ¼ 203). Decision-making styles were measured by Scott and Bruce's General Decision Making Style scale (GDMS), and judgmental self-doubt by Mirels et al.'s Judgmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 32 publications
8
38
1
1
Order By: Relevance
“…and may allow for the analysis of the relationship among the decision-making styles and other constructs. In this regard, it has been observed that avoidant and dependent styles are positively correlated with the self-reported ratings of stress (e.g., Allwood & Salo, 2012;Salo & Allwood, 2011); and that rational and avoidant styles are positively correlated with anxiety and depression (Schoemaker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…and may allow for the analysis of the relationship among the decision-making styles and other constructs. In this regard, it has been observed that avoidant and dependent styles are positively correlated with the self-reported ratings of stress (e.g., Allwood & Salo, 2012;Salo & Allwood, 2011); and that rational and avoidant styles are positively correlated with anxiety and depression (Schoemaker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, as for life satisfaction, although the processes of thinking and decision-making under stress have been extensively studied (see Starcke & Brand, 2012), the view on the relationship between perceived stress and cognitive styles can be adopted chiefly from the position of similar constructs, mainly decision-making styles. While Salo & Alwood (2011) reported no significant relationships between the rational or intuitive decision-making style and stress in police officers, Bavolar & Orosova (2015) found perceived stress to be negatively associated with the intuitive decision-making style and Lasikiewics (2015) reported its negative correlation with the rational thinking style. Correlations can depend on gender; stress was found to be more negatively associated with both the rational and experiential style in men than in women (Epstein et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The process of making a decision, however, is often stressful Janis and Mann 1977;Salo and Allwood 2011). The processes that individuals follow in making decisions often tend to differ from person to person (Galotti et al 2006;Riaz et al 2012;Williams and Esmail 2014).…”
Section: Toward An Understanding Of Decision Making Stylesmentioning
confidence: 99%